2022
DOI: 10.3390/ma15238562
|View full text |Cite
|
Sign up to set email alerts
|

Alloy Design and Fabrication of Duplex Titanium-Based Alloys by Spark Plasma Sintering for Biomedical Implant Applications

Abstract: Very often, pure Ti and (α + β) Ti-6Al-4V alloys have been used commercially for implant applications, but ensuring their chemical, mechanical, and biological biocompatibility is always a serious concern for sustaining the long-term efficacy of implants. Therefore, there has always been a great quest to explore new biomedical alloying systems that can offer substantial beneficial effects in tailoring a balance between the mechanical properties and biocompatibility of implantable medical devices. With a view to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Accordingly, these findings suggested that the synthetic paediatric disc fabricated in the synthetic paediatric spine was acceptable. Here, we also envisage that the beta titanium alloys having advantageous mechanical properties that could serve promising potential for the fabrication of paediatric spines and other biomedical devices [ 27 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, these findings suggested that the synthetic paediatric disc fabricated in the synthetic paediatric spine was acceptable. Here, we also envisage that the beta titanium alloys having advantageous mechanical properties that could serve promising potential for the fabrication of paediatric spines and other biomedical devices [ 27 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are other reports on biocompatible titanium alloys with a low Young’s modulus besides TiNbSn alloys [ 7 , 8 , 9 , 10 , 11 ]. TiNbSn alloys have been clinically applied in hip replacement stems.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, the difference in the Young’s moduli of implants and the human cortical bone leads to a disproportionate stress distribution, resulting in pain and bone atrophy after surgery [ 6 ]. To resolve this problem, new titanium alloys, such as TiMoZrTa, TiMoZrSi, and TiZrTaSn alloys, have been developed that possess a low Young’s modulus in combination with biocompatibility and strength, and they have shown excellent material properties and favorable results in preclinical studies have been reported [ 7 , 8 , 9 , 10 , 11 ]. In our institute, the development of a near-β-type TiNbSn alloy with a low Young’s modulus of <50 GPa was speculated to reduce stress shielding and thigh pain [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ti-based alloys are significant for many different applications in addition to biomedicine, for example, in the automotive and aerospace industries. Their outstanding biocompatibility, extraordinary corrosion resistance, and high mechanical strength allow these alloys to be successfully used in biomedical applications [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the titanium–aluminum–vanadium (Ti-6Al-4V) alloy has long been employed in such applications, the V and Al released from the alloy could have harmful effects [ 7 , 8 , 9 , 10 , 11 , 12 ]. Al +3 and V +5 are released as free radicals, interact with the bloodstream, and possibly trigger harmful responses in humans, which increases the risk of developing Alzheimer’s disease [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%